Assessment of the Activity Parameters on Trichomonas vaginalis in Iraqi Women - Ali Mohammed, Baraa; Mohammed Hussein, ashjan; Hussein Jameel, Ali; Frimpong, Prince Opuni (Al-Salam Journal for Medical Science, 2024)
Vaginal infections are predominantly caused by Trichomonas vaginalis, bacterial vaginosis, and Candida infection. These infections are particularly concerning among pregnant women, potentially leading to adverse outcomes, including miscarriage. This study aimed to investigate the association between Trichomonas vaginalis infection and hormonal and immune parameters (Vitamin D and Thyroid Stimulating Hormone (TSH) levels). A cross-sectional study was conducted between September 2022 and October 2023. A total of 92 women participated, including 67 patients with recurrent vaginitis (characterized by burning, itching, and discharge) and 25 healthy controls. High vaginal swabs and 5 ml of venous blood were collected from each participant. Serum levels of Vitamin D, TSH, and inflammatory cytokines were measured using immunofluorescence techniques. Women infected with Trichomonas vaginalis had significantly elevated serum Vitamin D levels (P=0.0144), while the differences in TSH levels between the two groups were not statistically significant. Although associations between TSH, Vitamin D, and Trichomonas vaginalis infection were observed, these correlations did not reach statistical significance. This study suggested that Trichomonas vaginalis infection may be associated with increased serum Vitamin D levels in affected women. The lack of a significant change in TSH levels and its weak association with the infection indicate a complex interplay between hormonal balance and vaginal infections. Further research is needed to explore the implications of these findings, particularly in the context of infertility and immune modulation during vaginal infection.